Labor market shocks and monetary policy - Serdar Birinci; Fatih Karahan; Yusuf Mercan; Kurt See (Bank of Canada, 2023)
We develop a heterogeneous-agent New Keynesian model featuring a frictional labor market with on-the-job search to quantitatively study the positive and normative implications of employer-to-employer (EE) transitions for inflation. We find that EE dynamics played an important role in shaping the differential inflation dynamics observed during the Great Recession and COVID-19 recoveries, with the former exhibiting subdued EE transitions and inflation despite both episodes sharing similar unemployment dynamics. The optimal monetary policy prescribes a strong positive response to EE fluctuations, implying that central banks should distinguish between recovery episodes with similar unemployment but different EE dynamics.
Keywords: E12; E24; E52; J31; J62; J64; 330; Business fluctuations and cycles; Inflation and prices; Labour markets; Monetary policy